Police Knowledge, Attitudes, and Beliefs About Opioid Addiction Treatment and Harm Reduction: A Survey of Illinois Officers - Reichert, Jessica (Journal of drug issues, 2025)
Police officers encounter individuals with opioid use disorder (OUD) during their routine work and are often called to the scene of overdoses. Despite this frequency, officer knowledge and attitudes about addiction, treatment, and harm reduction vary. Views held by officers, and the extent of their knowledge, can impact the decisions they make regarding people with OUD, yet our understanding of these factors is limited. Using stratified random sampling, we surveyed 248 officers from 27 Illinois police departments on their knowledge of addiction and the means to address it. We performed descriptive and regression analyses to examine differences based on officer characteristics. We found a high proportion of officers lacked knowledge of addiction, treatment, and harm reduction. Our findings suggest the need for police training to improve understanding of addiction. Community collaboration and coordination of resources may give officers the tools to better address OUD, reduce harm, and decrease overdose.